2017
DOI: 10.1016/j.chemosphere.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulatory responses to cadmium in reference and historically metal contaminated Gammarus fossarum (Crustacea, Amphipoda) populations

Abstract: In order to better understand the variable sensitivities of crustaceans to metals, we investigated the impact of cadmium exposure in 3 populations of Gammarus fossarum from different rivers of France. The first population lives in a Cd-contaminated river from a geochemical background, while the others inhabit Cd-free sites. Osmoregulation, a relevant biomarker to evaluate crustacean health following metal contamination, was used as a proxy to evaluate the intra- and inter-populationnal sensitivities to Cd. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For ion uptake from fresh water, the involvement of VHA has been implicated in several groups of crustaceans (reviews in Charmantier et al, 2009 ; McNamara and Faria, 2012 ; Weihrauch and O’Donnell, 2015 ; Leone et al, 2017 ). These include crayfish ( Zare and Greenaway, 1998 ), decapod crabs ( Putzenlechner et al, 1992 ; Onken and Putzenlechner, 1995 ; Riestenpatt et al, 1995 ; Weihrauch et al, 2001 ; Genovese et al, 2005 ; Weihrauch et al, 2005 ; Tsai and Lin, 2007 ), palaemonid shrimps ( Faleiros et al, 2010 ; Boudour-Boucheker et al, 2014 , 2016 ; Lucena et al, 2015 ; McNamara et al, 2015 ; Faleiros et al, 2017 ), the amphipod Gammarus fossarum ( Dayras et al, 2017 ), calanoid copepods ( Lee C. E. et al, 2011 ; Johnson et al, 2014 ; Gerber et al, 2016 ), and neonates of the branchiopod Daphnia magna ( Bianchini and Wood, 2008 ). In the copepod Eurytemora affinis complex, VHA activity shows both an evolutionary increase in recently derived freshwater populations, relative to saline populations, and an acclimatory increase under freshwater conditions for both saline and freshwater populations ( Lee C. E. et al, 2011 ).…”
Section: Ion Uptake In Crustaceansmentioning
confidence: 99%
“…For ion uptake from fresh water, the involvement of VHA has been implicated in several groups of crustaceans (reviews in Charmantier et al, 2009 ; McNamara and Faria, 2012 ; Weihrauch and O’Donnell, 2015 ; Leone et al, 2017 ). These include crayfish ( Zare and Greenaway, 1998 ), decapod crabs ( Putzenlechner et al, 1992 ; Onken and Putzenlechner, 1995 ; Riestenpatt et al, 1995 ; Weihrauch et al, 2001 ; Genovese et al, 2005 ; Weihrauch et al, 2005 ; Tsai and Lin, 2007 ), palaemonid shrimps ( Faleiros et al, 2010 ; Boudour-Boucheker et al, 2014 , 2016 ; Lucena et al, 2015 ; McNamara et al, 2015 ; Faleiros et al, 2017 ), the amphipod Gammarus fossarum ( Dayras et al, 2017 ), calanoid copepods ( Lee C. E. et al, 2011 ; Johnson et al, 2014 ; Gerber et al, 2016 ), and neonates of the branchiopod Daphnia magna ( Bianchini and Wood, 2008 ). In the copepod Eurytemora affinis complex, VHA activity shows both an evolutionary increase in recently derived freshwater populations, relative to saline populations, and an acclimatory increase under freshwater conditions for both saline and freshwater populations ( Lee C. E. et al, 2011 ).…”
Section: Ion Uptake In Crustaceansmentioning
confidence: 99%
“…Despite being a very sensitive marker, the response is very dependent on the types of exposure. In G. fossarum , Issartel et al observed an overexpression of gill Na + /K + ATPase in Cd impacted animals, while Gismondi et al showed inductions of these enzymes after long-term exposure to Cu of G. fossarum . Harris and Santos observed significant higher Na + /K + ATPase activities in posterior gills of crabs Ucides cordatus and Callinectes danae after contamination with three different heavy metals, and Reddy et al and Comoglio et al observed inhibitions (the latter concentration-dependent) in Na + /K + ATPase enzymatic activity after pesticide exposures in the crab Barytelphusa guerini and the shrimp Litopenaeus vannamei , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Deleterious effects of Cd on DNA integrity have been reported in several decapods (Frías-Espericueta et al, 2022). Histological analyses have shown an increased cell proliferation in the gills of gammarids, shrimps, and crabs following Cd exposure (Dayras et al, 2017). Moreover, Zn and Cd may, among other things, cause osmoregulation disorders, the induction of reactive oxygen species (ROS), and a decrease in ionoregulation (Frías-Espericueta et al, 2022;Ren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The species Gammarus fossarum is of particular interest to freshwater ecosystems due to their function as a detritivore, giving them a central role in freshwater ecosystems, and in particular in aquatic food webs as an important link between detritus and fish (Filipović Marijić et al, 2016;Kunz et al, 2010). They also have a wide distribution, are present in abundance, and, because of their size and ease of identification, they are easy to sample and handle in the laboratory (Dayras et al, 2017;Issartel et al, 2010b;Lebrun et al, 2017). In addition, they are known to be net accumulators of metals, which explains why gammarids are regularly used to monitor aquatic contaminations (Besse et al, 2013;Conti et al, 2016;Lebrun et al, 2015).…”
mentioning
confidence: 99%